Pengaruh Perkembangan Teknologi Terhadap Tenaga Kerja Di Sektor Industri Manufaktur Otomotif - Tio Ramadan; Anas Nurrahman; Hilmi Rabbani Ferdi; Fajar Jumadil Fadillah; Yudi Prastyo (JURNAL ILMIAH NUSANTARA, 2025)
Rapid technological developments in the Industrial Revolution 4.0 era have brought significant changes to the manufacturing industry sector, including the automotive industry. This transformation is marked by the application of automation, digitalization, artificial intelligence, and the Internet of Things (IoT) which directly affect the structure and needs of the workforce. This study uses a literature review method by examining several accredited national journals to identify the positive and negative impacts of technological advances on the workforce. The results of the study show that technological developments make a positive contribution in the form of increased production efficiency, product quality, and the emergence of new, more skilled types of work. However, on the other hand, technology also causes a reduction in conventional labor, competency gaps, and adaptation pressures for workers. Therefore, a competency development strategy and continuous training are needed so that the workforce is able to adapt to today's industrial needs. These findings are expected to be a reference in making employment policies and developing human resources in the automotive manufacturing sector.